Results of the IX International Spectroradiometer Intercomparison and impact on precise measurements of new photovoltaic technologies. (8th October 2020) - Pavanello, D.; Galleano, R.; Zaaiman, W.; Ankit, M.; Kouremeti, N.; Gröbner, J.; Hoogendijk, K.; Po, M.; Lisbona, E.F.; Alius, W.; Dosenovicova, D.; Kroeger, I.; et al.
Abstract: Today's variety of photovoltaic (PV) technologies imposes new challenges to laboratories and industries to precisely measure the performance of devices and, consequently, to accurately estimate the energy yield once installed in a specific location. Spectroradiometry has become a key discipline for metrology applied to PV: Spectral irradiance is one of the three parameters according to which solar simulators are classified according to IEC 60904‐9; precise spectrum measurements are a key factor in the spectral mismatch calculation. Finally, energy rating calculations according to IEC 61853 involve spectral irradiance conditions different than the AM1.5G standard spectrum. To tackle these issues, since 2011, the International Spectroradiometer Interlaboratory Comparison (ISRC) takes place annually in different locations of Europe with the participation of laboratories, research institutes, and industry partners to assess spectral measurement capabilities and share good measurement practices and protocols. In this paper, several results of the 9th ISRC 2019 are presented, looking in particular at the impact on characterization of new technologies like organic devices (OPV), dye‐sensitized (DSSC), and perovskites. Abstract : In June 2019, the 9th ISRC took place at the Observatory of Saint‐Veran, grouping participants from world‐leading laboratories to industry. Concerning impact of spectrum measurements on the characterisation of PV devices, good agreement was found for c‐Si market technologies, but further effort is needed for new ones (Perovskites, OPV, DSSC) in order to reduce measurement uncertainties. An upgrade of measurement capabilities will be needed by several laboratories to meet requirements of the new upcoming standard IEC 60904‐9.